Решение
{ cos(x)*√(sin(y)) = 0 (1)
{ 2cos²(x) = 2sin²(y) - 1 (2)
(1): cos(x)*√(sin(y)) = 0
а) cosx = 0 ⇒ x = pi/2 + pi*k, где k∈ Z
тогда в (2):
2cos²(x) = 2sin²(y) - 1
0 = 2sin²(y) - 1
sin²(y) = 1/2
sin(y) = 1/√2
![y=(-1)^n\cdot \frac{ \pi}{4}+ \pi\cdot n y=(-1)^n\cdot \frac{ \pi}{4}+ \pi\cdot n](https://tex.z-dn.net/?f=y%3D%28-1%29%5En%5Ccdot+%5Cfrac%7B+%5Cpi%7D%7B4%7D%2B+%5Cpi%5Ccdot+n++)
, где n∈Z
sin(y)= -1/√2
![y=(-1)^{m+1}\cdot \frac{ \pi}{4}+ \pi\cdot m y=(-1)^{m+1}\cdot \frac{ \pi}{4}+ \pi\cdot m](https://tex.z-dn.net/?f=y%3D%28-1%29%5E%7Bm%2B1%7D%5Ccdot+%5Cfrac%7B+%5Cpi%7D%7B4%7D%2B+%5Cpi%5Ccdot+m++)
, где m∈Z
б)
y = pi*n, где n∈Z
тогда в (2):
2cos²(x) = 2sin²(y) - 1
2cos²(x) = -1
cos²(y) = -1/2 - не существует
Ответ: x = pi/2 + pi*k;
![y=(-1)^n\cdot \frac{ \pi}{4}+ \pi\cdot n y=(-1)^n\cdot \frac{ \pi}{4}+ \pi\cdot n](https://tex.z-dn.net/?f=y%3D%28-1%29%5En%5Ccdot+%5Cfrac%7B+%5Cpi%7D%7B4%7D%2B+%5Cpi%5Ccdot+n++)
, где n∈Z
![y=(-1)^{m+1}\cdot \frac{ \pi}{4}+ \pi\cdot m y=(-1)^{m+1}\cdot \frac{ \pi}{4}+ \pi\cdot m](https://tex.z-dn.net/?f=y%3D%28-1%29%5E%7Bm%2B1%7D%5Ccdot+%5Cfrac%7B+%5Cpi%7D%7B4%7D%2B+%5Cpi%5Ccdot+m++)
, где m∈Z